GEOMORPHOLOGICAL AND SEQUENCE STRATIGRAPHIC VARIABILITY IN WAVE-DOMINATED, SHOREFACE-SHELF PARASEQUENCES - Hampson G.J.; Storms J.E.A. (My University, 2003)
Physical stratigraphy within shoreface-shelf parasequences contains a detailed, but virtually unstudied, record of shallow-marine processes over a range of historical and geological timescales. Using high-quality outcrop data sets, it is possible to reconstruct ancient shoreface-shelf morphology from clinoform surfaces, and to track the evolving morphology of the ancient shoreface-shelf. Our results suggest that shoreface-shelf morphology varied considerably in response to processes that operate over a range of timescales. (1) Individual clinoform surfaces form as a result of enhanced wave scour and/or sediment starvation, which may be driven by minor fluctuations in relative sea level, sediment supply and/or wave climate over short timescales (101 -103 years). These external controls cannot be distinguished in vertical facies successions, but may potentially be differentiated by the resulting clinoform geometries. (2) Clinoform geometry and distribution changes systematically within a single parasequence, reflecting the cycle in sea level and/or sediment supply that produced the parasequence (102 -105 years). These changes record steepening of the shoreface-shelf profile during early progradation and maintenance of a relatively uniform profile during late progradation. Modern shorefaces are not representative of this stratigraphic variability. (3) Clinoform geometries vary greatly between different parasequences as a result of variations in parasequence stacking pattern and relict shelf morphology during shoreface progradation (105 -108 years). These controls determine the external dimensions of the parasequence.
Keywords: CLINOFORM; FACIES MODEL; PARASEQUENCE; SHELF; SHOREFACE; SHORELINE TRAJECTORY